2020
DOI: 10.1111/1750-3841.15152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polar compounds in fried palm oil on liver lipid metabolism in C57 mice

Abstract: Polar components (PCs) are produced during the frying of oil, affecting the quality of edible oil and posing a hazard to human health. In this study, C57 mice were fed a high‐fat (HF) diet containing purified PCs for nine weeks. Their effects on lipid metabolism and liver function in animals were analyzed. Our results indicated that the contents of total PCs and saturated fatty acid increased from 6.07 ± 0.6% and 58.27 ± 0.35% to 19.17 ± 1.8% and 69.91 ± 0.51%, respectively (P < 0.01). PC intake resulted an 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have found that abnormalities of mitochondrial morphology and function may be associated with fatty liver accumulation [27][28]. Meanwhile, Li et al [9] compared the effect of PO and low-fat diet on the expression level of lipid breakdown-related genes and found that the PPAR-α expression levels of the PO-treated group were signi cantly downregulated. The nuclear receptor protein-PPARs-are fundamentally important for energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that abnormalities of mitochondrial morphology and function may be associated with fatty liver accumulation [27][28]. Meanwhile, Li et al [9] compared the effect of PO and low-fat diet on the expression level of lipid breakdown-related genes and found that the PPAR-α expression levels of the PO-treated group were signi cantly downregulated. The nuclear receptor protein-PPARs-are fundamentally important for energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Palm oil contains higher ratios of SFA to MUFA and PUFA than other cooking oils [8]. Previously, Li et al [9] studied the effects of palm oil diet compared with low-fat diet on the expression level of lipid breakdown-related genes and found that palm oil showed signi cantly downregulated hepatic PPAR-α expression levels. When PPARα is inhibited by fatty acids, FA oxidation and the ensuing ATP production are diminished.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hu et al (2020) conducted a comparative intermittent frying trials using palm stearin and oil blend containing a mixture of high oleic sunflower oil and canola oil, and depicted that the combined level of primary and secondary oxidation in palm stearin was two folds lower than that of blended oil. According to Su et al (2020), the oil types and frying cycles could also influence the fate of acrylamide in fried products. The consumption of naturally stable oil for frying is not only found to be cost-effective but also overcomes public concern towards oils produced from genetically modified crops (Qi et al, 2020).…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…It is a known fact that the intake of used oils through food poses the tendency of health incidences. Recently published findings revealed the effect of consuming overheated oils which lead to higher occurrence of non-alcoholic fatty liver disease based on the intervention studies using human hepatic carcinoma cell line (HepG2) (Chatuphonprasert et al, 2020) and C57 mice (Li et al, 2020). In a study comparing the effect of heated canola and palm olein on gut microflora in rats, Ruan et al (2020) found that the latter oil significantly stimulates the proliferation of beneficial probiotics namely Lactobacillus and Roseburia.…”
Section: P R E S S Nutrition and Healthmentioning
confidence: 99%
“…The TPC content is an accurate and reliable index used to evaluate the quality of frying oils (Ahmad Tarmizi et al ., 2019). Many countries, namely Spain, Italy, Portugal, Germany, France, Belgium, Switzerland and the Netherlands, have established the maximum allowance of 24–27% for TPCs (Li et al ., 2020). Nevertheless, measuring TPC alone to evaluate oil degradation is inapplicable to oils that contain abundant quantities of natural diglycerides (DGs) (Ahmad Tarmizi et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%